Antigen expression on recurrent meningioma cells - Vranič, Andrej (Radiology and oncology (Ljubljana), 2010)
Introduction. Meningiomas are intracranial brain tumours that frequently recur. Recurrence rates up to 20% in 20 years for benign meningiomas, up to 80% for atypical meningiomas and up to 100% for malignant meningiomas, have been reported. The most important prognostic factors for meningioma recurrenceare meningioma grade, meningioma invasiveness and radicality of neurosurgical resection. The aim of our study was to evaluate the differences in antigenic expression on the surface of meningioma cells between recurrent and non-recurrent meningiomas. Methods. 19 recurrent meningiomas and 35 non-recurrent meningiomas were compared regarding the expression of MIB-1 antigen, progesterone receptors, cathepsin B and cathepsin L, using immunohistochemistry. Results. MIB-1 antigen expression was higher in the recurrent meningioma group (p=0.001). No difference in progesterone receptor status between recurrent and non-recurrent meningiomas was confirmed. Immunohistochemical intensity scores for cathepsin B (p= 0.007) and cathepsin L (p<0.001) were both higher in the recurrent than in the non-recurrent meningioma group. Conslusions. MIB-1 antigen expression is higher in recurrentcompared to non-recurrent meningiomas. There is no difference in expression of progesterone receptors between recurrent and non-recurrent meningiomas. Cathepsins B and L are expressed more in recurrent meningiomas.
Keywords: antigeni; Antigeni novotvorb; Antigens, Neoplasm; Cathepsins; Immunohistochemistry; Imunohistokemija; Katepsini; Meningeal Neoplasms; Meningealne novotvorbe; Meningeom; Meningioma; meningiomi; Neoplasm Recurrence, Local; Novotvorba, ponovitev lokalna; rak (medicina); Receptorji progesteronski; Receptors, Progesterone; Retrospective Studies; Retrospektivne študije